2020
DOI: 10.3390/ijerph17030898
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Bout of Intense Exercise on Some Executive Functions

Abstract: The present study examined the effects of an exhaustive exercise on executive functions by using the Stroop Color Word Test (SCWT), Trail Making Test (TMT), A and B, and simple Reaction Time (RT). Thirty adults agreed to participate; 15 participants had a mean age of 24.7 years ± 3.2 Standard Deviation (SD, Standard Deviation) (group YOUNG), while the remaining 15 had a mean age of 58.9 years ± 2.6 SD (group OLD). Each subject performed the cognitive tasks at rest and blood lactate was measured (pre); each sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Thus, our ndings buttress the idea that peripherally muscle expressed lactate, which is able to cross the blood brain barrier via monocarboxylate transporters, is utilized as "fuel" for cognitive processes [30,40,[49][50][51][52][53][54][55][56][57]. However, such a nding is not universal since negative associations between peripheral blood lactate levels and attentional performance [58], and executive functions [59] have been reported, too. The divergent ndings between our study and the study of Coco and colleagues [58] could be, at least, partly explained by difference in study methodology (e.g., exercise regime [SIT protocol vs. maximal multistage discontinuous incremental cycling test, used cognitive test [d2 test vs.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, our ndings buttress the idea that peripherally muscle expressed lactate, which is able to cross the blood brain barrier via monocarboxylate transporters, is utilized as "fuel" for cognitive processes [30,40,[49][50][51][52][53][54][55][56][57]. However, such a nding is not universal since negative associations between peripheral blood lactate levels and attentional performance [58], and executive functions [59] have been reported, too. The divergent ndings between our study and the study of Coco and colleagues [58] could be, at least, partly explained by difference in study methodology (e.g., exercise regime [SIT protocol vs. maximal multistage discontinuous incremental cycling test, used cognitive test [d2 test vs.…”
Section: Discussionsupporting
confidence: 58%
“…For example, Perciavalle et al ( 2014 , 2016 ) have found that attentive capabilities and performance after an exhaustive exercise worsened, most likely due to increased blood lactate levels. Coco et al (2020) also found increased reaction time and blood lactate after intense exercise, which were strongly correlated. On the other hand, Mroczek et al (2011) found an initial decrease in reaction time despite increased blood lactate during and after volleyball sets.…”
Section: Introductionmentioning
confidence: 65%
“…However, recent evidence on mammalian muscle has shown that reduced pH may have little influence on muscle contraction, and it is most likely the inorganic phosphate which is the major cause of muscular fatigue (Posterino et al, 2001; Westerblad, 2002 , 2016 ). In the same way, there are currently contradictory opinions ( Coco et al, 2009 , 2016 , 2020 ; Duncan et al, 2017 ; Mroczek et al, 2011 ; Tanaka et al, 2018 ; Tsukamoto et al, 2016 ) on how high blood lactate levels (induced either by exhaustive exercise or by an intravenous infusion of a lactate solution) may affect various psychomotor processes, especially simple reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…This cognitive domain includes aspects of attention such as intensity (sustained attention and alertness) and selectivity (divided, focused, and broad attention). In particular, the ability to analyze a large amount of information is a characteristic of broad attention, while selective attention permits one to discriminate between stimuli and to select some of them even in the presence of distracting stimuli [18].…”
Section: Studies On Cognitionmentioning
confidence: 99%